Jn 8,25 au risque de l'herméneutique Les versions anciennes - Rico, Christophe 1962- (2023)
In the following pages we shall examine the Syriac, Coptic and Latin versions of Jn 8:25. A special attention will be paid to the Vulgate translation, which in this particular verse has often been criticized. In order to fully appreciate its soundness, one has to understand the interpretative rules which Saint Jerome used to apply in his translation.
Cet article examine les versions syriaques, coptes et latines de Jn 8,25. Souvent décriée par les exégètes, l’interprétation qu’offre ici la Vulgate est évaluée en fonction des principes de traduction qui caractérisent la version de saint Jérôme.